Persistent Spinal Pain Syndrome: A Proposal for Failed Back Surgery Syndrome and ICD-11. Issue 4 (27th January 2021) - Christelis, Nick; Simpson, Brian; Russo, Marc; Stanton-Hicks, Michael; Barolat, Giancarlo; Thomson, Simon; Schug, Stephan; Baron, Ralf; Buchser, Eric; Carr, Daniel B; Deer, Timothy R; Dones, Ivano; et al.
Abstract: Objective: For many medical professionals dealing with patients with persistent pain following spine surgery, the term Failed back surgery syndrome (FBSS) as a diagnostic label is inadequate, misleading, and potentially troublesome. It misrepresents causation. Alternative terms have been suggested, but none has replaced FBSS. The International Association for the Study of Pain (IASP) published a revised classification of chronic pain, as part of the new International Classification of Diseases (ICD-11), which has been accepted by the World Health Organization (WHO). This includes the term Chronic pain after spinal surgery (CPSS), which is suggested as a replacement for FBSS. Methods: This article provides arguments and rationale for a replacement definition. In order to propose a broadly applicable yet more precise and clinically informative term, an international group of experts was established. Results: 14 candidate replacement terms were considered and ranked. The application of agreed criteria reduced this to a shortlist of four. A preferred option—Persistent spinal pain syndrome—was selected by a structured workshop and Delphi process. We provide rationale for using Persistent spinal pain syndrome and a schema for its incorporation into ICD-11. We propose the adoption of this term would strengthen the new ICD-11 classification. Conclusions: This project is important to those in the fields of pain management, spine surgery, and neuromodulation, as well as patients labeled with FBSS. Through a shift in perspective, it could facilitate the application of the new ICD-11 classification and allow clearer discussion among medical professionals, industry, funding organizations, academia, and the legal profession.